English in Asia: Power, Identity, and Inequality - Patil, V. (University of Jaffna, 2025)
English occupies a paradoxical position in Asia, serving as both a vehicle for socio-economic mobility and a source of cultural and linguistic tension. The study aims to critically trace the historical development of English in the region, from its colonial origins to its present status as a global language; to analyze its influence on social mobility and the widening of socio-economic inequalities; and to study its impact on local cultures, native languages, and traditional knowledge systems amid tensions between global and local forces. Using case studies from India, China, and Southeast Asia, the article shows that while English facilitates access to global opportunities, it also reinforces social divides and marginalizes indigenous identities. It further highlights how English often threatens linguistic and cultural diversity, raising concerns about homogenization. However, it also demonstrates how Asian societies creatively adapt and appropriate English to assert agency within global contexts. The article argues for a balanced approach that maximizes the pragmatic benefits of English while safeguarding linguistic and cultural diversity, promoting a more inclusive and culturally sensitive model of development across Asia.
Keywords: Globalization; Linguistic policy; Cultural identity; Inclusive development; Global Discourse